Identity and participation in a workplace English language training classroom in Thailand: a community of practice perspective - Taylor, Pimsiri (2014)
This ethnographic study investigates identity and participation in a workplace English language training classroom in Thailand. As a practitioner’s enquiry, the research methods of participation observation, interviews and questionnaires were employed in exploring a 40-hour training classroom which acts as a workplace community of practice for both the teacher and the student participants. Through the lens of communities of practice (Lave and Wenger, 1991), the research shows the significance, despite common assumptions of shared interests and choice to participate in communities of practice, of gatekeeping and legitimacy defined by the Human Resources department. As a formal corporate training classroom with an outside language instructor, there is evidence of multiple identities and forms of participation. The identities of expert newcomers, semi-expert newcomers as well as non-expert old-timers pose questions about forms of participation, especially legitimate peripheral participation and full participation, in the communities of practice model. Reversal of identities in the classroom between teacher and students emphasise pedagogical roles in the community. Identities are negotiated and constructed amongst the interrelationships of legitimacy, power relations, and social structures of the community of practice. Within the different layers of social practice (classroom, organisation and Thai cultural and social norms), legitimation conflicts arise. English language proficiency, and skills and knowledge regarding the organisation and engineering, coupled with the role of ‘seniority’ in peer relationships expressed in the pseudo-sibling relationship in Thai culture, are common causes of tension. Individual participants must exercise their agency to negotiate their identities and power among these conflicts and tensions. Using both verbal and non-verbal language, language-related identities contribute to identity negotiation and construction. ‘Joker’ and ‘silent member’ identities suggest the use of humour and silence as a discursive practice. Code-switching from English to Thai enables language to be used as a shared repertoire in the community. Specific use of pronouns in Thai represents the identities of classroom participants. The research shows that language use and culture should be central to the analysis of identity and participation in communities of practice. The thesis concludes by discussing implications for researchers on communities of practice, and practitioners in English language corporate training and English for Specific Purposes.